The effect of low dose caffeine powder supplementation on serve speed, spike speed, and speed-endurance in elite sitting volleyball players: a randomized double-blind crossover study - Diedhiou, Azize Bingöl; Erkan, Dilara; Guler, Melek; Sar, Halit; Karakulak, İzzet; Eyüboğlu, Ender; Yıldırım, Ulas Can (Bmc, 2025)
BackgroundSitting volleyball relies heavily on upper-body strength and anaerobic capacity. Serve, spike, and speed-endurance are decisive skills, yet the ergogenic potential of low-dose caffeine in this Paralympic sport remains unclear.PurposeTo examine the acute effects of low-dose caffeine (3 mg/kg) supplementation on serve speed, spike speed, and speed-endurance in elite sitting volleyball players.MethodsUsing a randomized, double-blind, crossover design, 13 elite male athletes from the Turkish National Sitting Volleyball Team completed serve speed, spike speed, and speed-endurance tests under caffeine (CAF) and placebo (PLA) conditions.ResultsCaffeine intake produced a moderate improvement in serve speed (p = 0.028, d = 0.460); however, this effect did not remain statistically significant after Bonferroni correction (adjusted p = 0.084). No significant effects were observed for spike speed (p = 0.547, d = 0.166) or speed-endurance performance (p = 0.709, d = 0.111). Perceived exertion during the speed-endurance test was similarly high in both conditions.ConclusionsLow-dose caffeine may offer a trend toward improved serve performance, but the effect was not robust after statistical adjustment, and no benefits were observed for spike speed or speed-endurance. These findings highlight that caffeine's ergogenic effects are context-dependent and shaped by task complexity and sport-specific motor demands. Further research with larger and more diverse samples, genotype-based subgroups, and varied dosing strategies is warranted to clarify caffeine's role in adaptive sports.Trial registrationThe randomized controlled trial was retrospectively registered on 21/06/2025 at ClinicalTrials.gov, under the registration number NCT07056231.
Keywords: Caffeine 1; Sitting volleyball 2; Serve speed 3; Spike speed 4; Speed-Endurance 5